# If A + B + C = π, prove that

= sin2A + sin2B + sin2C

Using,

Sin2A = 2sinAcosA

= 2sinAcosA + 2sin(B+C)cos(B - C)
since A + B + C = π

= 2sinAcosA + 2sin(π - A)cos(B - C )
= 2sinAcosA + 2sinAcos(B - C)
= 2sinA{cosA + cos (B-C)}
( but cos A = cos { 180 - ( B + C ) } = - cos ( B + C )

And now using
= 2sinA{2sinBsinC}
= 4sinAsinBsinC

Now,

= sinA + sinB + sinC

Using,

Therefore,

= R.H.S

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Conditional Identities31 mins
All Standard Trigonometric Identities in Triangle35 mins
Important Questions on Standard trigo identities in triangle27 mins
Orthocentre and escribed circles48 mins
Circumcentre & its properties54 mins
Solution of Triangles | Test Yourself | QuizFREE Class
Incentre | Mastering important concepts51 mins
Stewart's Theorem46 mins
Interactive Quiz on Half angle formula, circumcircle and incircle48 mins
Centroid | Mastering important conceptsFREE Class
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

If A + B + C = π, prove that

RS Aggarwal - Mathematics

If A + B + C = π, prove that

RS Aggarwal - Mathematics